A relação Portugal – Timor-Leste nos discursos do Presidente e na imprensa - Ramos, Rui (2013)
The President of Portugal, Aníbal Cavaco Silva, performed between 20 and 22 May 2012 an official visit to East-Timor, coinciding with the celebrations of 10 years of independence of this country. During his stay, the President issued a set of seven official speeches. These express an official and personal point of view on the past, present and future relationship between Portugal and East-Timor. While institutional discourses, they shape the relationship between the two nations and as they circulate in the public sphere, they incorporate the potential to intersect with other discourses, to approach distant reality to the common citizen and to reificate intangible entities such as shared culture and history and the perceptions of empathy between the two peoples. The Portuguese press followed the official visit, as they contextualized and reconfigured these discourses. This paper performs an analysis of the main lines of development of the President’s speeches, their salient topoi and their inherent rhetoric, and identifies the most noticeable results of modalisation of journalism done by two national newspapers on the political, economic and social Timorese state of affairs and on the presidential speeches.